A review of milling stability using semi discretization method - AZOUI Cherifa; BENMOHAMMED Brahim (3rd International Conference in Mechanics (3rd ICM'2017), 2017)
Recently the investigation of periodic motion of the delayed functional differential equations (DDEs) and the associated variation systems become the focus of many studies. One of the most important motivations is the milling process analysis. Different techniques are used to obtain approximate solutions for the delayed functional differential equations (DDE). All these models used the stability lobe diagrams in order to choose the maximum axial depth of cut, for a given spindle speed associated with the chatter free machining. In this work, a semi discretization method is briefly explained and has been applied for 1-DOF (degree of freedom) and 2-DOF milling system in order to build the stability lobe diagrams.